Improvement of Surface Passivation of Tunnel Oxide Passivated Contact Structure by Thermal Annealing in Mixture of Water Vapor and Nitrogen Environment. Issue 10 (18th June 2019) - Zhang, Zhi; Liao, Mingdun; Huang, Yuqing; Guo, Xueqi; Yang, Qing; Wang, Zhixue; Gao, Tian; Shou, Chunhui; Zeng, Yuheng; Yan, Baojie; Ye, Jichun
Abstract : The effects of post‐crystallization annealing within various atmospheres on the surface passivation quality of tunnel oxide passivated contact (TOPCon) for crystalline silicon (c‐Si) solar cells are studied. The results provide an innovative method for improving the surface passivation of the as‐crystallized TOPCon structure by annealing at moderate temperatures ranging from 300 to 700 °C within a mixture of water vapor and nitrogen atmosphere. The wet nitrogen improves the implied open‐circuit voltages ( iV oc ) from 700–710 to ≈730 mV on average and reduces the single‐side reverse saturated recombination current density ( J 0 ) to 3.8 fA cm −2, which is much more effective than the so‐called forming‐gas annealing. In addition, the contact resistivity remains in low values of ≈5 mΩ cm 2, ensuring its application in the high‐efficiency c‐Si solar cell. Secondary ion mass spectroscopy provides the evidence that the enhanced surface passivation by the water vapor annealing results from the hydrogen incorporation, which is logically believed to passivate the defects in the oxide and c‐Si interface region. This study proposes a simple and cost‐effective technique to improve the surface passivation of TOPCon structure, which is suitable for the high‐efficiency c‐Si solar‐cell manufacture. Abstract : The post‐annealing of 300–700 °C within a mixture of water vapor and nitrogen atmosphere is proven to be an easy and cost‐effective technique to improve surface passivation of the tunnel oxide passivated contact structure, which reason is attributed to the incorporation and passivation of hydrogen at the polysilicon/silicon oxide/crystalline silicon interface.